Substance use among adolescent and young adult cancer survivors. Issue 11 (27th August 2015) - Milam, Joel; Slaughter, Rhona; Meeske, Kathleen; Ritt‐Olson, Anamara; Sherman‐Bien, Sandra; Freyer, David R.; Kuperberg, Aura; Hamilton, Ann S.
Abstract: Objective: Health‐promoting behaviors are recommended to childhood cancer survivors (CCS) to reduce late effects resulting from cancer treatment. Understanding factors associated with substance use is needed, especially among Hispanic CCS who are underrepresented in previous studies. The objective of this study is to examine substance use behaviors of recently treated Hispanic and non‐Hispanic CCS. Methods: One hundred ninety‐three Los Angeles County CCS who were diagnosed between 2000 and 2007 (54% Hispanic; mean age 19.9 years, SD = 2.8; mean age at diagnosis = 12.1, SD = 3.0; mean years since diagnosis = 7.8, SD = 2.0) provided self‐reported information on substance use, demographics, clinical factors, religiosity, and depressive symptoms. Risk and protective factors for substance use were examined using multivariable logistic regression. Results: Prevalence of 30‐day substance use was 11%, 25%, and 14% for tobacco, alcohol, and marijuana, respectively. In controlled regression models, age was positively associated with tobacco use, binge drinking, and polysubstance use (use of at least two of the three substances). Male gender, higher depressive symptoms, and higher socioeconomic status were associated with greater marijuana use. In addition, religiosity was negatively associated with the use of all substances. Conclusions: The prevalence rates for substance use in this ethnically diverse representative sample of CCS are lower than those observed in the general population. Older CCS were at higher risk of substance use, and depression was associated with greater marijuana use. No differences by ethnicity were observed. Interventions for substance use prevention/cessation among CCS may be most effective if implemented before the age of 21 years and address mental health as part of survivorship care. Copyright © 2015 John Wiley & Sons, Ltd.